Human psychophysiology. Laboratory session. - Kuznetsov, I. P.; Kachynska, T. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The manual may be used during “Human Psychophysiology” laboratory works for studying the basics of psychophysiological experiment design and interpretation. The manual is written taking into account the tasks of study course, which are specified by the program of higher education institutes. The manual has methodical recommendations for 11 laboratory works, with theoretical information, self-test questions and theme bibliography in each. The manual intended for natural science specialties students of full-time and postal tuition of higher education institutes.
Психофізіологія людини. Лабораторний практикум
Keywords: Psychophysiology; Heart rate variability method; ICA-analysis; Evoked potentials method; Memory; Attention